2019
DOI: 10.1016/j.apsb.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeting slug-mediated non-canonical activation of c-Met to overcome chemo-resistance in metastatic ovarian cancer cells

Abstract: Metastasis-associated drug resistance accounts for high mortality in ovarian cancer and remains to be a major barrier for effective treatment. In this study, SKOV3/T4, a metastatic subpopulation of ovarian cancer SKOV3 cells, was enriched to explore potential interventions against metastatic-associated drug resistance. Quantitative genomic and functional analyses were performed and found that slug was significantly increased in the SKOV3/T4 subpopulation and contributed to the high resistance of SKOV3/T4. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Furthermore, mesenchymal markers (i.e., Vimentin or N-Cadherin) decrease the polarity of cancer cells and accelerate migration and invasion 56,57 . Recently, the EMT process has been proposed as an important regulator of drug resistance [58][59][60] . Accumulating data have confirmed that mechanisms of resistance to sorafenib may involve the EMT and the Notch signaling pathway is a key regulator of the EMT process [61][62][63] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mesenchymal markers (i.e., Vimentin or N-Cadherin) decrease the polarity of cancer cells and accelerate migration and invasion 56,57 . Recently, the EMT process has been proposed as an important regulator of drug resistance [58][59][60] . Accumulating data have confirmed that mechanisms of resistance to sorafenib may involve the EMT and the Notch signaling pathway is a key regulator of the EMT process [61][62][63] .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, we tested whether SLUG was upstream of ITGB1. This too was plausible since others have reported SLUG to regulate integrins in keratinocytes [ 51 ], wound healing in the gut [ 52 ], and in ovarian cancer cells [ 53 ]. However, SLUG knockdown yielded no change in ITGB1 in our CTC models of HCC and CRPC.…”
Section: Discussionmentioning
confidence: 99%
“…CAL 27 and SCC-15 cell were seeded onto six-well plates and allowed to form confluent monolayer overnight. Next day, a wound was created by scraping the cell monolayer with 200 μL pipette tip as described previously 33 . The cultures were washed three times with fresh medium to remove debris and treated with varying dilutions of PEP06 (50, 100 and 200 μg/mL) or endostatin (100 μg/mL) for 48 h. The images of wounds were captured for each group at 0 and 48 h, and the gap width was analyzed using Image-Pro Plus 6.0 (Media Cybernetics, Rockville, MD, USA).…”
Section: Methodsmentioning
confidence: 99%